Supercriticality of the Dynamo Limits the Memory of the Polar Field to One Cycle - Kumar P.; Karak B.B.; Vashishth V. (My University, 2025)
The polar magnetic field precursor is considered to be the most robust and physics-based method for the prediction of the next solar cycle strength. However, to make a reliable prediction of a cycle, is the polar field at the solar minimum of the previous cycle enough or do we need the polar field of many previous cycles? To answer this question, we performed several simulations using Babcock-Leighton-type flux-transport dynamo models with a stochastically forced source for the poloidal field (α term). We show that when the dynamo is operating near the critical dynamo transition or only weakly supercritical, the polar field of cycle n determines the amplitude of the next several cycles (at least three). However, when the dynamo is substantially supercritical, this correlation of the polar field is reduced to one cycle. This change in the memory of the polar field from multiple to one cycle with the increase of the supercriticality of the dynamo is independent of the importance of various turbulent transport processes in the model. Our this conclusion contradicts the existing idea. We further show that when the dynamo operates near the critical transition, it produces frequent extended episodes of weaker activity, resembling the solar grand minima. The occurrence of grand minima is accompanied by the multicycle correlation of the polar field. The frequency of grand minima decreases with the increase of supercriticality of the dynamo. © 2021. The American Astronomical Society. All rights reserved..